Explaining European Union Lifelong Learning Policy: Globalisation and Competitiveness or Path Dependency and Citizenship? - John Holford (Adult Education Research Conference, 2008)
The European Union’s founding treaties and institutions determine that ‘markets’ frame its approach to lifelong learning, yet other more humanistic discourses, albeit secondary, have developed. This paper explores how and why.